2013
DOI: 10.1038/ni.2609
|View full text |Cite
|
Sign up to set email alerts
|

VAMP7 controls T cell activation by regulating the recruitment and phosphorylation of vesicular Lat at TCR-activation sites

Abstract: The mechanisms by which Lat (a key adaptor in the T cell antigen receptor (TCR) signaling pathway) and the TCR come together after TCR triggering are not well understood. We investigate here the role of SNARE proteins, which are part of protein complexes involved in the docking, priming and fusion of vesicles with opposing membranes, in this process. Here we found, by silencing approaches and genetically modified mice, that the vesicular SNARE VAMP7 was required for the recruitment of Lat-containing vesicles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
191
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(203 citation statements)
references
References 50 publications
8
191
1
3
Order By: Relevance
“…In conclusion, VAMP7 KO MEFs show phenotypes clearly related to the traffic of lipids and proteins known to reside in membrane domains. While these phenotypic traits do not preclude cell and organism life, 55,56 they may nevertheless induce profound signaling defects 20 which largely remain to explore. Further studies are required to address the impact of this mechanism in the organism and also how a v-SNARE which primarily mediates membrane fusion may also be required at earlier stages of membrane traffic like sorting of some components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, VAMP7 KO MEFs show phenotypes clearly related to the traffic of lipids and proteins known to reside in membrane domains. While these phenotypic traits do not preclude cell and organism life, 55,56 they may nevertheless induce profound signaling defects 20 which largely remain to explore. Further studies are required to address the impact of this mechanism in the organism and also how a v-SNARE which primarily mediates membrane fusion may also be required at earlier stages of membrane traffic like sorting of some components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, VAMP7 is involved in the transport of GLUT1 and Lat, two other membrane domain associated proteins. 19,20 Altogether, these findings led us to hypothesize a more direct contribution of VAMP7 in membrane organization and membrane domains homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…2011) put forward a role for LAT vesicles in TCR signaling, challenging previous studies that demonstrated the requirement of LAT plasma membrane oligomerization and cis phosphorylation (Houtman et al, 2006) for TCR signal transduction. Moreover, Larghi et al (2013) very recently proposed that a VAMP7-mediated LAT vesicle docking to the synapse was responsible for TCR signaling. In contrast, another recent work (Balagopalan et al, 2013), using a CD4-LAT chimeric protein, proposed that it is mainly plasma membrane LAT that is phosphorylated and incorporated into microclusters, with minor influence from its vesicular pool.…”
Section: Methodsmentioning
confidence: 99%
“…A v-SNARE (soluble N-ethylmaleimide-sensitive protein-attached protein receptor) protein VAMP7 guides these vesicles into the plasma membrane potentially by docking to the t-SNARE proteins, surprisingly, in a mechanism that does not involve actual membrane fusion. 14 These results suggest that components of the molecular machinery utilized in trafficking of synaptic vesicles in the neuronal synapse such as SNAREs and small Rab GTPases play an important role in the trafficking of subsynaptic vesicles in T cells to activate intracellular signaling pathways. However, the importance of vesicles in TCR signaling has been uncovered only recently and the identity and functions of these subsynaptic vesicles in T cell activation needs further investigation.…”
mentioning
confidence: 90%